Minors and Crime: Law and Criminological Analysis on Theft by Children (Case of Central Java, Indonesia) - Basuki, Astin Ratri Nur Anggraini; Sari, Indah Novita; Arifin, Ridwan; Nte, Ngboawaji Daniel (Law Research Review Quarterly, 2023)
Juvenile delinquency comes in many forms-one of which is theft. This delinquency is a social phenomenon with a continuation of criminology. Juvenile crimes are a major concern because children are generation of thenation. Children who commit criminal Acts certainly have both internal and external causes. The treatment of child criminals is part of the policy as a child protection effort as a form of law enforcement. Criminology plays an important role in this case because it is also called criminal sociology because it is the study of humans in its opposition to certain social norms. Criminology examines social symptoms in the field of crime occurring in the community or with the intent that the defendant has committed these crimes.